Hermite bicubic spline collocation method for Poisson's equations - Mihaela Puşcaş (Journal of Numerical Analysis and Approximation Theory, 2004)
In this paper is presented a bicubic spline collocation method for the numerical approximation of the solution of Dirichlet problem for the Poisson's equation. The approximating solution is effectively determined in a bicubic Hermite spline functions space by using a suitable basis constructed as a tensorial product of univariate spline spaces.